MODEL OF INFORMATION CULTURE FUTURE PHILOLOGIST (Pedagogy of Higher and Secondary Education, 2009)
In article is presented model of the information culture of the future philologist. She consists of such block: information culture of the relation information culture of the knowledges, information methodical culture and information culture of the interaction.
Keywords: information culture future philologist; model of the information culture of the future philologist